Fibroblast growth factor 18 stimulates chondrocyte proliferation by modulating FOXN2 to mitigate post-traumatic osteoarthritis in a mouse model - Huang, Zhusong; Zhao, Wenhan; Lan, Jinfu; Lin, Yu; Gao, Xi (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionFGF18 is linked to osteoarthritis (OA) progression, but its relationship with FOXN2 and its roles in post-traumatic osteoarthritis (PTOA) remain unclear.MethodsWe conducted comparative screening between PTOA and normal controls to assess FGF18 expression in articular cartilage. Functional studies examined FGF18 overexpression effects on chondrocyte proliferation and cartilage degradation. Intra-articular FGF18 delivery was performed in destabilized medial meniscus (DMM)-induced PTOA mice models.ResultsFGF18 expression was significantly downregulated in articular cartilage of PTOA patients compared to normal cases. FGF18 overexpression enhanced chondrocyte proliferation through BMP2 upregulation and attenuated cartilage degradation by suppressing CTX-II and catabolic factors (MMP13 and ADAMTS-5), while substantially promoting aggrecan synthesis. Intra-articular FGF18 delivery in DMM mice significantly reduced cartilage erosion and markedly decreased synovial thickening compared to saline-treated controls, with improved cartilage matrix integrity. FOXN2 expression was significantly upregulated in FGF18-knockout chondrocytes but restored upon FGF18 overexpression.DiscussionThese findings highlight that FGF18 mitigates PTOA progression by targeting FOXN2, promoting robust aggrecan synthesis, and substantially suppressing cartilage-degrading enzymes. Our study delineates a novel therapeutic axis for PTOA, emphasizing the distinct molecular mechanisms underlying trauma-driven cartilage pathology.